Eksplorasi Peran Peer Counselor dalam Pencegahan Bullying pada Remaja: Studi Kualitatif di Kota Tanjungpinang - Aniesaputri Junita; Ana Krisnawati; Rina Oktavia; Serly Serly; Nada Auliya; Nurul Mualimah; Zhavira Fiorent (Lembaga Pengembangan Kinerja Dosen, 2026)
Bullying remains a significant problem among adolescents and negatively affects their psychological well-being, social relationships, and academic development. To address this issue, a community service program was conducted to strengthen the role of peer counselors in preventing bullying among adolescents in Tanjungpinang City. The program involved 13 participants consisting of five peer counselors, three adolescents who had experienced bullying, and five healthcare professionals from the Youth Care Health Services Program (Program Pelayanan Kesehatan Peduli Remaja [PKPR]). The activities included educational sessions, interactive discussions, simulations, and mentoring to enhance participants' knowledge and skills in bullying prevention. Program evaluation was carried out through Focus Group Discussions (FGDs) and interviews to obtain feedback regarding the implementation of peer counselor roles after the activities. The evaluation identified five key roles of peer counselors, namely educator, active listener, early detection agent, motivator, and bridge. These roles contributed to improving adolescents' understanding of bullying prevention, providing emotional support, facilitating early identification of bullying cases, motivating victims, and connecting them with teachers, parents, and healthcare professionals for appropriate assistance. This community service program demonstrated that strengthening the capacity of peer counselors through education and mentoring can support bullying prevention efforts and foster a safer and more supportive school environment.